Dampak kepesertaan PBI terhadap konsumsi rumah tangga - Winda Tiarani; Adila Solida; Arnild Augina Mekarisce; Usi Lanita (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: The Contribution Assistance Recipients (PBI) program is a national health insurance scheme in which premiums are fully subsidized by the government for low-income and impoverished populations. Muaro Jambi Regency records the highest proportion of PBI participants (84.73%) in the BPJS Jambi Branch area, with Muara Kumpeh Puskesmas holding the highest PBI enrollment (22.45%) among all puskesmas in the regencyPurpose: To analyze the impact of PBI membership on household consumption patterns, including food consumption, non-food consumption, education expenditure, and tobacco expenditure. Method: Data analysis was performed using the Wilcoxon Signed Rank Test to determine differences in household consumption before and after PBI enrollment, with a significance threshold of p < 0.05.Results: Significant differences (p-value = 0.000 < 0.05) were found across all household consumption variables before and after PBI enrollment. (1) Food consumption increased from an average of IDR 1,061,263 to IDR 1,668,895 per month. (2) Non-food consumption increased from an average of IDR 790,105 to IDR 1,110,874 per month. (3) Education expenditure slightly decreased from an average of IDR 437,404 to IDR 421,011 per month (Z = -4.811), influenced by seasonal factors and inter-household variation. (4) Tobacco expenditure increased from an average of IDR 545,426 to IDR 628,316 per month (Z = -6.837). Conclusion: PBI membership significantly impacted household consumption patterns in the working area of Muara Kumpeh Puskesmas. Food and non-food consumption increased substantially, reflecting the economic benefit of reduced direct health expenditures. However, the increase in tobacco expenditure indicates that not all additional financial capacity was allocated to productive needs.   Keywords: Household Consumption; National Health Insurance; PBI.